2009
DOI: 10.1002/app.31665
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of water soluble cationic microgels by dispersion polymerization: Their performance in kaolin deposition onto fiber

Abstract: ABSTRACT:The water soluble cationic microgels (CMG), intramolecularly cross-linked cationic polymers of acrylamide (Am) and diallyldimethylammonium chloride (DADMAC), were synthesized with dispersion polymerization in the mixture of tert-butanol (TBA)/water in the presence N,N 0 -methylene-bisacrylamide (MBA) as the cross-linker, poly(N-vinylpyrrolidone (PVP) as the stabilizer and 2,2 0 -azobisisobutyronitrile (AIBN) as the initiator. The effects of monomer, cross-linker, initiator, and stabilizer concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…Nevertheless, the latter two effects predominated over the template effect as the DMD content was further increased. In addition, the optimum intrinsic viscosity was considerably higher in the present study than in previous studies, which indicated the merits of adding a template. The mass ratio between AM and DMD of 7:3 was preferred, considering the charge neutralization performance of TPDA.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…Nevertheless, the latter two effects predominated over the template effect as the DMD content was further increased. In addition, the optimum intrinsic viscosity was considerably higher in the present study than in previous studies, which indicated the merits of adding a template. The mass ratio between AM and DMD of 7:3 was preferred, considering the charge neutralization performance of TPDA.…”
Section: Resultscontrasting
confidence: 52%
“…To produce PDA, AM and DMD have been polymerized via solution polymerization, disperse polymerization and inverse emulsion polymerization . However, the aforementioned polymerization methods are limited by the random distribution of cationic units in the cationic polyacrylamide (CPAM) molecular chain.…”
Section: Introductionmentioning
confidence: 99%
“…Although acrylamide is a neutral monomer and does not contribute to the overall charge density of the lignin copolymer, this slight increase in charge density is associated with the fact that acrylamide most probably helped cross‐linked DADMAC to lignin . The high reactivity ratio of acrylamide suggests that acrylamide reacts with other acrylamide monomers, whereas DADMAC monomers with a relatively low reactivity ratio have higher tendency to react with acrylamide than with DADMAC monomers . Thus, the higher concentration of acrylamide present in the reaction mixture, the more DADMAC monomer can be incorporated into the copolymer, increasing the overall charge density of the copolymer .…”
Section: Resultsmentioning
confidence: 99%
“…The improvement in the solubility of the lignin copolymer was attributed to the presence of water soluble component on the lignin copolymer backbone, that is, AM and DADMAC. However, the results show that the copolymerization was not sufficiently efficient to make the lignin copolymer 100 % water soluble …”
Section: Resultsmentioning
confidence: 99%
“…Once particles have been formed, they absorbed monomer from the continuous phase and the reaction mainly took place within the particles 6–9. It has been well reported about dispersion polymerization of cationic PAM with poly(dimethylaminoethyl methacrylate methyl chloride), poly(acryloyl‐oxyethyl trimethyl ammonium chloride), poly(2‐acrylamido‐2‐methyl‐propanesulfonic acid) etc, as the stabilizer 10–14…”
Section: Introductionmentioning
confidence: 99%